Peran Kepala Sekolah dalam Peningkatan Mutu Pendidikan di SMA Negeri 2 Gerung - Alaydrus, Abdul Kadir (AHKAM, 2023)
This study aims to identify and describe the role of the principal in improving the quality of education at SMA Negeri 2 Gerung, West Lombok. The research method used in this study was descriptive qualitative research using observation techniques and also interviews with school principals and other school residents in the research area. The results obtained explain that the principal has carried out various efforts and has played a role in improving the quality of education at SMA Negeri 2 Gerung. Efforts made include various important roles in terms of leadership and also school management both for teachers, students, infrastructure, human resources, extracurriculars and also other school supporters. The conclusion in this study is that the role of the school principal as a managerial is very important in improving the quality of education and the role of the school principal has been carried out by; 1) planning programs, 2) organizing programs, 3) activating programs, 4) monitoring and evaluation, 5) developing culture.